PENGARUH PERPINDAHAN PEDAGANG KAKI LIMA TERHADAP KEUNTUNGAN DI TAMAN TINGKIR KOTA SALATIGA - Setyaningrum, Ramdani Putri; Putri, Winda Octaviani; Suryani, Gabriela Christin (EP FEB UNS, 2018)
Taman Tingkir is a public space built by Salatiga government. Currently it is used family recreative place. The Taman Tingkir attracts many people to do activities in that place. This research was conducted to examine the impact of the to Taman Tingkir on the profit of streets vendors. This study collects primary data by interview, survey, and observation, as well as photograph documentation. The data collected from 30 street vendors in Taman Tingkir and was analyzed using Validation Test, Wilcoxon Test and Ordinal Regression Test. Our result showed that the movement of the street vendors impact to the increase of number of consumers, but not to profit, production capacity, and omzet. There is no correlation between number of consumers to the profit earned by the street vendors.Keywords: Taman Tingkir, Street Vendors, Profit, Public SpaceJEL Classification: H42, D74